Effects of Visual Feedback Complexity on the Performance of a Movement Task for Rehabilitation. Issue 2 (4th March 2021) - Sanford, Sean; Liu, Mingxiao; Selvaggi, Thomas; Nataraj, Raviraj
Abstract: This study investigated the effects of visual feedback (VF) complexity on movement performance to potentially optimize the design of VF-based rehabilitation. We evaluated the effects of VF complexity on performance of the two-legged squat during training with concurrent (real-time) VF and short-term retention with no VF. Four VF cases were employed to train spatial positioning of the thigh segment in unique combinations of complexity (simple, complex) and representation of body-discernibility (abstract, representative). Eighteen able-bodied subjects attempted to minimize the error between individual body segment positions and a target trajectory during concurrent VF and short-term retention tests. Complex-representative VF demonstrated greater potential for training with increased performance consistency in both motion and muscle activity patterns.